EXTH-29. GALECTIN-3 AS A POTENTIAL THERAPEUTIC TARGET IN RECURRENT ATYPICAL AND MALIGNANT MENINGIOMA. (11th November 2019) - Das, Arabinda; Martinez Santos, Jaime; Kanginakudru, Indira; McDonald, Daniel G; Kosnik Infinger, Libby; Vandergrift III, William; Varma, Abhay; Vanek, Kenneth N; Lindhorst, Scott; Patel, Sunil; Cachia, David
Abstract: Atypical and malignant meningiomas are rare tumors that unlike WHO I meningiomas are characteristically more aggressive in nature and are associated with higher recurrence risks of recurrence. In fact despite aggressive treatment of malignant meningiomas, the average 5-year survival rates are in the range of 30% to 60%. Still the standard of care for atypical and malignant meningiomas (AM and MM) has yet to be established. Our laboratory data demonstrated that galectin-3 (Gal-3), a multifunctional β-galactoside-binding protein, is highly expressed in AM and MM as compared to normal tissue. However, the biological functions of Gal-3 in meningioma cells are not fully understood. To address this, we used either small interfering RNA (siRNA) to knock down Gal-3 expression or Gal-3 inhibitor, TD139 to suppress Gal-3 expression in in vitro cell culture model. Silencing or inhibiting of Gal-3 expression significantly decreased the protein levels of urokinase-type plasminogen activator receptor (uPAR) as well as uPAR's downstream signaling transduction pathway, including phosphorylation of AKT. In both cases, we found that silencing of Gal-3 or inhibiting Gal-3 expression decreased the proliferative activity, and migratory potential of AM and MM cells. Furthermore, we demonstrated that TD139 inhibits MM growth in an in vivo xenograft MM model. Taken together, our results suggest that Gal-3 modulates uPAR expression and that Gal-3 may be a potential therapeutic target for the treatment of atypical and malignant meningiomas.